Tibolone Induces Serotonin, Estrogen, and Progesterone Receptor Expression but not Contractile Response to Serotonin in the Rat Uterus - Oropeza, M.; Calzada, C.; Guerra-Araiza, C.; Bazan-Perkins, B.; Mendoza-Espinoza, J. A.; Campos-Lara, M. G. (Hormone and Metabolic Research, 2013)
Most studies on the effect of tibolone on the uterus have focused on the endometrium dismissing the importance of the myometrium. The aim of the present study was to investigate some estrogen-like actions of tibolone in the uterus assessed by: 1) the expression of estrogen, progesterone, and serotonin receptors, and 2) the myometrial contraction induced by serotonin. Estradiol (250 μg), progesterone (50 mg), or testosterone (25 mg) pellets were implanted to ovariectomized rats. Tibolone (0.5 mg/day) was orally administered. An implanted pellet containing vehicle or an equivalent volume of water p.o., were used as controls. Sixty days after beginning the treatments, rats were killed and uterus removed. One horn was processed to evaluate estrogen-alpha, progesterone A and B, and serotonin-2A receptors expression, and the other one was used for studying contraction to serotonin and 60 mM potassium solution. The present data showed that tibolone-induced expression of estrogen, progesterone, and serotonin receptors, but did not induce uterine contractile response to either serotonin or potassium solution. These findings suggest that, in the uterus, tibolone may exert molecular estrogenic actions such as the induction of receptor expression, but not a physiological response as the estrogen-dependent contraction to serotonin.
Keywords: tibolone; serotonin; estrogenic actions; myometrial response; receptor expression